Hong Kong regime transformation at the crossroads: from the politics - administration and social capital perspectives - Moon, M. Jae; Gage, Robert W. (2003)
After Hong Kong returned to China, it experienced both subtle and significant changes in various arenas including its bureaucratic system, its politics, and in its civil society. These changes gradually lead to regime transformation. This article examines regime transformation in Hong Kong from two theoretical perspectives: politics - administration relations and state-civil society relations. Two cases which constitute salient issues today, the Right of Abode and the Falun Gong cases, were selected to illustrate the direction of Hong Kong regime transformation from both theoretical perspectives. The two cases suggest a possibility that Hong Kong might be gradually coming under more political/party influence from the Beijing government. They also suggest the institutionalization of a more centralized political system in Hong Kong, while it continues to maintain a relatively high level of social capital development with significant civil group activities. - Reproduced.
Keywords: Public administration - Hong Kong; Public administration